Water Hauling and Girls' School Attendance : Some New Evidence from Ghana - Nauges, Celine; Strand, Jon (World Bank, Washington, DC, 2013)
In large parts of the world, a lack of home tap water burdens households as the water must be brought to the house from outside, at great expense in terms of effort and time. This paper studies how such costs affect girls' schooling in Ghana, with an analysis based on four rounds of the Demographic and Health Surveys. Using Global Positioning System coordinates, it builds an artificial panel of clusters, identifying the closest neighbors within each round. The results indicate a significant negative relation between girls' school attendance and water hauling activity, as a halving of water fetching time increases girls' school attendance by 2.4 percentage points on average, with stronger impacts in rural communities. The results seem to be the first definitive documentation of such a relationship in Africa. They document some of the multiple and wide population benefits of increased tap water access, in Africa and elsewhere.